2018
DOI: 10.1002/psp.2222
|View full text |Cite
|
Sign up to set email alerts
|

The spatial dynamics of race in the transition to university: Diverse cities and White campuses in U.K. higher education

Abstract: Using exceptionally detailed administrative data on all 412,000 students attending university in the United Kingdom in 2014–2015 combined with spatial census data from 2011, we explore for the first time how the ethnic composition of where students grow up is linked to where they attend university. We calculate a “diversity score” for every U.K. university, which is then compared with the ethnic diversity of the surrounding area, allowing us to explore the institutional geography of ethnicity in U.K. universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…Whilst Black and minority ethnic students typically come from hometowns that are more diverse than the university they attend (Gamsu, Donnelly, & Harris, 2018) this is not always the case. For those participants who did not, the experience of coming to a White university was quite different.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst Black and minority ethnic students typically come from hometowns that are more diverse than the university they attend (Gamsu, Donnelly, & Harris, 2018) this is not always the case. For those participants who did not, the experience of coming to a White university was quite different.…”
Section: Resultsmentioning
confidence: 99%
“…Donnelly and Gamsu (2019) have identified and reflected on so-called "geometries of power" that shape and reinforce uneven spatial mobilities and social reproduction among young people. This suggests that pathways to education, particularly higher education, are mandated by expectations, patterned by class, gender, and particularly race, especially when reflecting on the whiteness of many university campuses (Gamsu et al, 2019). Other work shows how elite mobilities and networks shape and frame educational opportunities.…”
Section: (Some) Key Themes In Geographies Of Education Researchmentioning
confidence: 99%
“…In comparison to other studies, which demonstrated distress associated with COVID-19 among healthcare workers (Braquehais et al, 2020), most of the participants in the current study were not directly concerned about COVID-19. Although the ethnicity of participants in the current study was not captured, universities in Northern Ireland are the least diverse in the UK (Gamsu et al, 2019), with predominantly white students (Higher Education Statistics Agency, 2021). The impact of COVID-19 has highlighted ethnic disparities (Williamson et al, 2020), and the capture of ethinicity would be recommended in a future study.…”
Section: Limitationsmentioning
confidence: 99%